Pengaruh inisiasi menyusu dini terhadap praktik menyusui 1 bulan pertama - Legawati Legawati; Djaswadi Dasuki; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: The period of the first month of life is a critical moment for the sustainability of breastfeeding practices. Therefore optimal efforts are needed to maintain the breastfeeding practices. Early initiation of breastfeeding can help increase maternal confidence and support psychological condition of mothers in order to continue breastfeeding practices.Objective: To evaluate the impact of the early initiation of breastfeeding on breastfeeding practices in the first month of infant life.Method: The study was observational with cohort prospective study design using quantitative and qualitative approaches. Samples were 106 pairs of mothers and babies. The group from Pahandut Public Health Center (PHC) consisted of 53 women with early initiation of breastfeeding (exposed group) and the group from Tangkiling PHC consisted of 53 women without early initiation of breastfeeding (non exposed group). In both groups, dissemination on early initiation of complete breastfeeding and exclusive breastfeeding practices followed with one month breastfeeding practices was given. The quantitative data analysis was done in three stages. In addition, qualitative data analysis used exploration of in depth interview.Results: The result of mutivariable analysis with modeling showed that there was a significant relationship between early initiation of breastfeeding and breastfeeding practices in the first month of life (by controlling the variables of the decision to breastfeed, nipple condition, residence and gestational age) that could give contribution as much as 49% for breastfeeding practices in the first month of life. The result of in depth interview showed that breastfeeding practices were highly infuenced by information obtained by the women when checking up their pregnancy so that the decision to breastfeed could be made in advance and the women perceived the beneft of breastfeeding practices for her and her infant’s health. There were some reasons why the mother did not give complete breastfeeding, among others were the abnormal nipple condition and the mother’s fear on her child’s health for preterm baby.Conclusion: Breastfeeding practices in the first month of life occured more in mothers who practiced early initiation of breastfeeding than in those who did not. Mothers with at term delivery, nipple normal condition, breastfeeding decision prior to delivery, and residence in rural areas had greater chance of practicing breastfeeding in the first month of life.